(-2)(3*4+2(-2)(-5)) = -2(12+20) = -2(32) = -64
Answer:
1.53x−14.23
Step-by-step explanation:
<em>simplify: </em>
5.03x−8.03−(3.5x+6.2)
<em>Distribute the Negative Sign:</em>
=5.03x−8.03−1(3.5x+6.2)
=5.03x−8.03−1(3.5x)+(−1)(6.2)
=5.03x−8.03−3.5x−6.2
<em>Combine Like Terms:</em>
=5.03x−8.03+−3.5x−6.2
=(5.03x−3.5x)+(−8.03−6.2)
=1.53x−14.23
Answer:
![f(g(x))=\dfrac{|x|+1-||x|-1|}{2}](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%5Cdfrac%7B%7Cx%7C%2B1-%7C%7Cx%7C-1%7C%7D%7B2%7D)
Step-by-step explanation:
The most straightforward way is direct substitution of g(x) for x in f(x):
![f(g(x))=\dfrac{|x|+1-||x|-1|}{2}](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%5Cdfrac%7B%7Cx%7C%2B1-%7C%7Cx%7C-1%7C%7D%7B2%7D)
Okay, take a look at diagram 1 (I know it's rubbish I did it on paint :D), this shows all the information you've given in the question. The two coordinates and the distance between them.
Now if we draw additional lines on this diagram, we can make a right-angled triangle (this is on diagram 2). We can also work out the lengths of the additional sides because we know both coordinates at the end-points of the additional lines.
Finally because this is a right-angled triangle, Pythagoras' theorem must apply to its sides meaning
![( \sqrt{10} )^2 = (x-4)^2 + 3^2](https://tex.z-dn.net/?f=%28%20%5Csqrt%7B10%7D%20%29%5E2%20%3D%20%28x-4%29%5E2%20%2B%203%5E2)
![10 = (x-4)^2 + 9](https://tex.z-dn.net/?f=10%20%3D%20%28x-4%29%5E2%20%2B%209)
![(x-4)^2 = 1 \Rightarrow x-4 = 1](https://tex.z-dn.net/?f=%28x-4%29%5E2%20%3D%201%20%5CRightarrow%20x-4%20%3D%201)
therefore x=5.
Answer:
X=±8
Step-by-step explanation:
x²=64
x²=8²
X=±✓8²
X=±8